A Solvent Regulated Hydrogen Bond Crosslinking Strategy to Prepare Robust Hydrogel Paint for Oil/Water Separation. (5th September 2021) - Bai, Zhongxiang; Jia, Kun; Liu, Chenchen; Wang, Lingling; Lin, Guo; Huang, Yumin; Liu, Shuning; Liu, Xiaobo
Abstract: Hydrogel modified porous matrix with the super‐wetting surface (i.e., super‐hydrophilic/underwater super‐oleophobic) is ideal for oil/water separation. However, the deterioration in mechanical strength and separation efficiency during the swelling process and complicated synthesis procedure limits its industrial application. In this study, a strategy of using ethanol to dynamically regulate the hydrogen bond crosslinking between polyvinyl alcohol (PVA) and tannic acid (TA) is proposed to prepare a "hydrogel paint", which can be simply applied on the porous substrate surface by different one‐step operations (dipping, brushing, spraying, etc.) without additional cross‐linking. The underline mechanism is attributed to the re‐establishment of intermolecular hydrogen bond mediated cross‐linking between PVA and TA during ethanol evaporation. Consequently, the resultant hydrogel coating exhibits ultra‐high strength (>10 MPa), swelling volume stability, and excellent oil‐water separation efficiency (>99%). This study will provide new insights into the scalable fabrication of hydrogel‐coated porous materials for oil/water separation in industrial scenarios. Abstract : A strategy of using ethanol to dynamically regulate the hydrogen bond crosslinking between polyvinyl alcohol and tannic acid is proposed to prepare a "hydrogel paint", which can be applied on the porous substrate surface by different one‐step operations (dip, brush, spray, etc.). The super‐hydrophilicity, underwater super‐oleophobicity of hydrogel renders resultant composites with high performance in oil‐water separation.